Khesari Dal: A Food or a Dreadful Poison and Its Prevention and Detection by Chromatographic Method - Chakraborti, I.; Salhan, R.N. (Asian Journal of Chemistry, 2010)
Khesari pulse is cultivated in all parts of India, which contains a toxic amino acid β-N-oxalyl amino-L-alanine (BOAA), which causes a deadly disease lathyrism, a crippling action on human beings.